CILIATED VULVAR CYST IN A 13-YEAR-OLD GIRL- CASE REPORT - Sima, Aneta; Naunova, Vesna; Simeonova Krstevska, Slagjana; Dabeski, Drage; Jovcheski, Lazo; Risteski, Toni; Krsteska, Blagica (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2024)
Vulvar cysts are rare, mostly benign lesions in childhood, originating from Miller's embryonic tissue and associated with progesterone action. The interior of the cysts is lined with columnar epithelium with cilia. They can be asymptomatic until they reach a size that causes heaviness and pressure on the surrounding tissue and aesthetic deformity of the vulva. Case report: A 13-year-old girl presented with a large elongated cystic structure originating from the right labia majora of the vulva, with a length of about 20 cm, without significant symptoms, except for discomfort in the external genitalia. The cyst was surgically removed and the histopathological findings confirmed the existence of a ciliary vulvar cyst, originating from Miller's structures. After the operation, the cosmetic result was excellent and the young patient felt relieved. Conclusion: Vulvar cysts are a rare finding in childhood and puberty, but they can also reach large sizes. The treatment is surgical excision, which provides a cure, correction of the normal anatomy of the vulva, and histological confirmation of the diagnosis.
Keywords: Vulvar cyst; Millers structure; cilia